The Answer to the Question
is below this banner.
Here's the Solution to this Question
To determine if the function is invertible, we prove that it is a bijection, i.e it is both one-to-one and onto
If f(x)=f(y), then x=y i.e
x+1=y+1 x=y+1-1 x=y Thus f(x) is injective
Surjective / onto
f(x)=x+1, but x=y-1 f(x)=(y-1)+1 f(x)=y Thus f(x) is surjective.
f(x) is bijective since it is both injective and surjective, hence it is invertible
y=x+1 x=y-1 Thus the inverse of f(x) is given by: f¯¹(y)=y-1 or g(y)=y-1